Women in Shipbuilding, 1941 (United Kingdom, 1941)
1941 1939-1945 "Women in Shipbuilding, 1941" [HFR0047], 1941 This collective agreement between the Shipbuilding Employers' Federation and the Confederation of Shipbuilding and Engineering Unions covered the employment of women in shipbuilding and ship-repairing establishments for the duration of the war. The agreement covers wage rates, hours and welfare facilities. The only jobs deemed unsuitable for women are heavy manual labour and processes involving work with lead.